IMPLEMENTATION OF LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION IN SHARIA ECONOMIC PERSPECTIVE - Kadir, Amiruddin (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to discuss how the application of the law in protecting consumers and from a religious point of view, namely Islamic law. The existence of a consumer protection law is able to regulate the production of business actors so that they do not do things that can harm consumers. It is very worrying because the position of consumers here is very weak, given the lack of consumer knowledge and awareness on each side, both business actors and consumers. This study focuses on the application of UUPK in protecting the rights of consumers, demanding compensation from business actors if consumers are harmed. The method used in this research is library research or literature review, which collects data from the literature and other sources that support and relate to the discussion in this study. The results show that the application of Law Number 8 of 1999 concerning Consumer Protection (UUPK) is in line with Islamic economics, where this law is equally prioritizing the safety and comfort of consumers. In the UUPK it is also emphasized that one of the rights of consumers in article 4 paragraph (c) is the right to correct, clear and honest information regarding the conditions and guarantees of goods and or services, this is also recommended in Islam not to be fraudulent, honest and not prejudice weighing scales or deceiving